2005
DOI: 10.1111/j.1365-2133.2005.06430.x
|View full text |Cite
|
Sign up to set email alerts
|

Additive impairment of the barrier function by mechanical irritation, occlusion and sodium lauryl sulphate in vivo

Abstract: Physical irritants (friction, abrasive grains, occlusion) and detergents such as SLS represent a significant irritation risk and should be minimized, especially when acting together, as shown in our TRIT model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 50 publications
2
51
0
2
Order By: Relevance
“…In general, the tenside SLS possesses an exsiccation effect on the SC [45] . However, after initial exsiccation 1 h after patch removal hyperhydration was observed by capacitance measurement on day 1 after a 24-hour single SLS exposure [69] .…”
Section: Sc Hydrationmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, the tenside SLS possesses an exsiccation effect on the SC [45] . However, after initial exsiccation 1 h after patch removal hyperhydration was observed by capacitance measurement on day 1 after a 24-hour single SLS exposure [69] .…”
Section: Sc Hydrationmentioning
confidence: 99%
“…However, the exposure model and the evaluation methods are important variables influencing the outcome in irritancy testing [43,44] . Combining detergents and physical irritants creates an additive effect on SC barrier impairment [45,46] . Tandem repeated irritation tests (TRITs) demonstrated that combined mechanical irritation, SLS and occlusion cause complementary effects on the epidermal barrier disruption [45] .…”
Section: Irritation and Skin Barrier Integrity And Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the tandem repeated irritation test [11], several authors investigated the irritant potential of some specific combinations of irritants [12,13,14,15,16] reviewed in Kartono and Maibach [17]. Several years back, an overadditive effect of skin irritation after tandem application of SLS and toluene was demonstrated in contrast to applications of each irritant alone [18].…”
Section: Introductionmentioning
confidence: 99%
“…Achieving protective levels of anti-tetanus immune responses following antigen application to ultrasound-pretreated skin, in the absence of SDS in the coupling medium, or adjuvant, shows the promise of ultrasound for skin immunisation, and further study with other antigens and in other species is merited. For ultrasound-assisted skin permeabilisation, SDS is often included in the coupling medium at 1% w/v, (Tezel et al, 2004;Mitragotri & Kost 2001;Tezel et al, 2005), despite the fact that it is a skin irritant (Agner & Serup 1990), especially when applied concomitantly with other irritants (Fluhr et al, 2005). However, we show for the first time the feasibility of using low-frequency ultrasound for skin immunisation, in the absence of SDS.…”
Section: Topical Antigen Application To Intact Skin In the Absence Ofmentioning
confidence: 77%